Video cameras on wild birds. - Rutz, C; Bluff, L; Weir, A; Kacelnik, A (2007)
New Caledonian crows (Corvus moneduloides) are renowned for using tools for extractive foraging, but the ecological context of this unusual behavior is largely unknown. We developed miniaturized, animal-borne video cameras to record the undisturbed behavior and foraging ecology of wild, free-ranging crows. Our video recordings enabled an estimate of the species' natural foraging efficiency and revealed that tool use, and choice of tool materials, are more diverse than previously thought. Video tracking has potential for studying the behavior and ecology of many other bird species that are shy or live in inaccessible habitats.